Design and Simulation of an Extendable Wheel Chair. - Rutaraka Gideon (Kabale University, 2023)
People with walking disabilities are denied the luxury of accessing elevated places in the while using their wheelchairs. Some of these people rely on attendees to access these places. Others try to access these places on their own which is tedious. In this paper, a wheelchair with a double scissor mechanism is proposed that will help wheelchair users to comfortably access elevated places, The proposed wheelchair is first conceptualized to come up with the conceptual design consisting of a chair, mobile platform and a double scissor mechanism. The proposed wheelchair components are then designed and the 3D model prepared in solid works. The designed components include; Scissor Jinks, lead screw and a nut The prepared model is then imported into ADAMS and motion analysis is carried out. The displacement, velocity and acceleration graphs are generated showing the movement of the chair in the Y axis. Finite element analysis of the model is also carried out in solid works. The static stress and static displacement graphs are also generated. All the results generated using the different CAE software's are then discussed.